A billion cups: The diversity, traditional uses, safety issues and potential of Chinese herbal teas. (10th August 2018) - Fu, Yao; Yang, Jin-chao; Cunningham, Anthony B.; Towns, Alexandra Maria; Zhang, Yu; Yang, Hua-ying; Li, Jian-wen; Yang, Xue-fei
Abstract: Ethnopharmacological relevance: Herbal teas have long been consumed by Chinese people for preventive and/or therapeutic healthcare. Although herbal teas are widely consumed by many cultural groups in different regions of China, no thorough review has been undertaken to assess the diversity of the country's herbal tea usage. This literature review, complemented by a quantitative survey in an important tea market in Kunming, begins to fill this knowledge gap. Aims of the study: The study aims to summarize the current knowledge of plant species used as herbal teas by different cultural groups in different regions of China, with a focus on the teas' perceived traditional healthcare functions, related phytochemical/pharmaceutical research, and safety issues. Materials and methods: The study involved a comprehensive literature review and a market survey. The literature review was based on published ethnobotanical studies of herbal teas in China. We searched the Web of Science™, ELSEVIER, the China National Knowledge Infrastructure (CNKI) and the China Science and Technology Journal Database to locate relevant studies (including journal articles, Masters/PhD dissertations and books) that were published before March 2017. A species list was compiled based on the review and supplemented with information retrieved from the Scifinder database (https://scifinder.cas.org ) and the Chinese Pharmacopoeia (2010). A Use Value Index was employed for ranking the most cited species. Based on the 29 most cited species, we discussed the current research status in relation to healthcare benefits and safety concerns of herbal teas in China. To better understand the current status of the herbal tea market in China, we also surveyed 136 tea vendors at the Xiongda Tea Market in Kunming. Information gathered from the survey included the species sold, the sale prices and the form of the herbal tea product. Results: The literature identified 759 plant species used as herbal tea in China and the market survey identified an additional 23 species. Most of the species used were from the Leguminosae, Compositae and Lamiaceae families. Twenty two provinces and fourteen ethnic minority groups have records on the consumption of herbal teas. Southern China uses up to 82% of the total species, and 211 out of 759 species are used by minority groups. Thirty categories of traditional healthcare functions are linked with herbal teas, with clearing away heat, relieving toxicity and suppressing cough being the most important functions. There is phytochemical/pharmaceutical evidence to support the claimed healthcare benefits of some Chinese herbal teas. Although Chinese herbal teas are generally safe to consume, overdoses of some herbal teas and some unapproved mixtures of species may cause health risks. Based on our market survey, the prices of most herbal teas range between 100 and 200 RMB (US$15–30) per kg. Conclusions: A rich array of herbal tea species with various traditional healthcare functions have long been used in China, and as such there is a huge market potential for Chinese herbal teas. More pharmaceutical/phytochemical research is needed to assess a wide range of perceived healthcare benefits of Chinese herbal teas. Our research highlights the need to study herbal teas through an ethnopharmacological perspective and by employing a holistic approach, which requires greater consideration of traditional knowledge in the pharmacological research design. Product safety and sustainability issues should also be considered, so the traditional applications of herbal teas can be transformed to efficient health boosting functional products. Graphical abstract: